IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM MENDUKUNG KEPUTUSAN PEMILIHAN REKOMENDASI HANDPHONE - Yustiqomah, Evita Citra; Lutfina, Erba; Saraswati, Galuh Wilujeng; Mahmud, Wildan (Science Technology and Management Journal, 2025)
In the rapidly evolving digital era, the demand for mobile phones is increasing, with a wide range of specifications and price points available. PT. Topsell Raharja Indonesia, as one of the leading mobile phone retailers, faces challenges in providing fast and accurate recommendations that align with the needs of prospective buyers. The manual phone selection process currently used by sales staff often leads to errors in decision-making, resulting in service delays and customer dissatisfaction. Therefore, this study aims to develop a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) to assist the store in recommending optimal mobile phones based on specific criteria. The AHP method is utilized to analyze and compare several key criteria—including price, RAM capacity, camera quality, battery life, performance, and design—in order to determine priority rankings for phone selection. The results demonstrate that the proposed system improves the efficiency of recommendations, reduces selection errors, and accelerates the customer service process. The implementation of the AHP method enables objective and accurate suggestions, achieving up to 98% accuracy. By systematically calculating the weight of each criterion, the system generates optimal alternatives tailored to the preferences and needs of prospective buyers